Healthy Neighborhoods: Walkability and Air Pollution - Marshall, Julian D. (National Institute of Environmental Health Sciences, 2009)
BACKGROUND: The built environment may influence health in part through the promotion of physical activity and exposure to pollution. To date, no studies have explored interactions between neighborhood walkability and air pollution exposure. METHODS: We estimated concentrations of nitric oxide (NO), a marker for direct vehicle emissions), and ozone (O(3)) and a neighborhood walkability score, for 49,702 (89% of total) postal codes in Vancouver, British Columbia, Canada. NO concentrations were estimated from a land-use regression model, O(3) was estimated from ambient monitoring data; walkability was calculated based on geographic attributes such as land-use mix, street connectivity, and residential density. RESULTS: All three attributes exhibit an urban–rural gradient, with high walkability and NO concentrations, and low O(3) concentrations, near the city center. Lower-income areas tend to have higher NO concentrations and walkability and lower O(3) concentrations. Higher-income areas tend to have lower pollution (NO and O(3)). “Sweet-spot” neighborhoods (low pollution, high walkability) are generally located near but not at the city center and are almost exclusively higher income. POLICY IMPLICATIONS: Increased concentration of activities in urban settings yields both health costs and benefits. Our research identifies neighborhoods that do especially well (and especially poorly) for walkability and air pollution exposure. Work is needed to ensure that the poor do not bear an undue burden of urban air pollution and that neighborhoods designed for walking, bicycling, or mass transit do not adversely affect resident’s exposure to air pollution. Analyses presented here could be replicated in other cities and tracked over time to better understand interactions among neighborhood walkability, air pollution exposure, and income level.